Competing tradeoffs between increasing marine mammal predation and fisheries harvest of Chinook salmon. Issue 1 (December 2017) - Chasco, Brandon; Kaplan, Isaac; Thomas, Austen; Acevedo-Gutiérrez, Alejandro; Noren, Dawn; Ford, Michael; Hanson, M.; Scordino, Jonathan; Jeffries, Steven; Marshall, Kristin; Shelton, Andrew; Matkin, Craig; et al.
Abstract Many marine mammal predators, particularly pinnipeds, have increased in abundance in recent decades, generating new challenges for balancing human uses with recovery goals via ecosystem-based management. We used a spatio-temporal bioenergetics model of the Northeast Pacific Ocean to quantify how predation by three species of pinnipeds and killer whales (Orcinus orca ) on Chinook salmon (Oncorhynchus tshawytscha ) has changed since the 1970s along the west coast of North America, and compare these estimates to salmon fisheries. We find that from 1975 to 2015, biomass of Chinook salmon consumed by pinnipeds and killer whales increased from 6, 100 to 15, 200 metric tons (from 5 to 31.5 million individual salmon). Though there is variation across the regions in our model, overall, killer whales consume the largest biomass of Chinook salmon, but harbor seals (Phoca vitulina ) consume the largest number of individuals. The decrease in adult Chinook salmon harvest from 1975–2015 was 16, 400 to 9, 600 metric tons. Thus, Chinook salmon removals (harvest + consumption) increased in the past 40 years despite catch reductions by fisheries, due to consumption by recovering pinnipeds and endangered killer whales. Long-term management strategies for Chinook salmon will need to consider potential conflicts between rebounding predators or endangered predators and prey.